Conflicts of Interest and Market Illiquidity in Bankruptcy Auctions: Theory and Tests - Strömberg, Per (Journal of Finance, 2000)
I develop and estimate a model of cash auction bankruptcy using data on 205 Swedish firms. The results challenge arguments that cash auctions, as compared to reorganizations, are immune to conflicts of interest between claimholders but lead to inefficient liquidations. I show that a sale of the assets back to incumbent management is a common bankruptcy outcome. Sale‐backs are more likely when they favor the bank at the expense of other creditors. On the other hand, inefficient liquidations are frequently avoided through sale‐backs when markets are illiquid, that is, when industry indebtedness is high and the firm has few nonspecific assets.